Isothermal real-time RT-RPA for Machupo virus detection: Field-adaptable sensitivity comparable with laboratory PCR - Marina A. Kapitonova; Anna V. Shabalina; Igor S. Sukhikh; Artemiy A. Volkov; Vladimir G. Dedkov; Anna S. Dolgova (PLoS ONE, 2026)
Isothermal nucleic acid amplification methods, such as recombinase polymerase amplification (RPA), are becoming increasingly vital as diagnostic platforms for neglected tropical diseases by enabling rapid and accurate detection in under-resourced regions. We developed a real-time RT-RPA assay for Machupo virus (MACV), the causative agent of Bolivian hemorrhagic fever, and directly compared it to a real-time RT-PCR assay targeting the same viral sequence fragment. The methods were evaluated across critical parameters: limit of detection (LOD), tolerance to single-nucleotide substitutions, multiplexing capability, and adaptability to multiple MACV genetic variants. The LOD was identical for both assays: 5 × 10 3 copies/ml of armored RNA particles. They differed in terms of input RNA (copies/reaction): 100 (PCR) versus 20 (RPA). The real-time RT-RPA assay was further validated on a portable device, demonstrating its potential for field-deployability for point-of-care applications.